A curious sociology (Sociologisk Forskning, 2023)
In the first sociology course I ever took, our first reading was The sociological imagination. Mills’s (2000) writings on the differences between personal troubles and public issues, the influence of historical developments on individual experiences, and his overarching emphasis on thinking sociologically opened my eyes to a new way of seeing, understanding, and acting in the world. The sociological imagination Mills describes encourages us to question common-sense, to wonder why our societies look the way they do, and to imagine different lives, choices, and ideals. However, in his discussion of the sociological imagination, Mills (2000:5) presupposes that we (and our fellow citizens) are inherently curious, suggesting that “what [we] feel [we] need is a quality of mind that will help [us]… to achieve lucid summations of what is going on in the world and what may be happening within [ourselves].” At least for me, this was not necessarily something I felt as an 18-year-old in my second semester of university when I first encountered Mills. Yet, as we read and discussed Mills, Mead, Addams, Weber, Smith, and others, this feeling developed and grew. I became more curious, inspired to continue reading and learning sociology. Sociology helped me develop a better understanding of myself and the world around me at the same time as I found that sociology enabled me to choose amongst broader lines of actions, ideals, and life paths. This text considers the role that sociology can (and should) play in helping us understand our world. I begin with this personal anecdote, on my experience of encountering sociology, because it (unsurprisingly) heavily influences my answer to the question of how I, as a young sociologist, view the role and future of sociology. Here, I will argue that we should understand sociology as a practice characterized by curiosity. I suggest that this could have at least two potential benefits. First, a sociology saturated with curiosity would be an inherently relevant sociology. Although I (and presumably, other readers of this journal) may read sociological texts, discuss sociological theory, and do sociological research on an (almost) daily basis, sociology lacks the cultural resonance of disciplines like economics and psychology in the newspapers, public debates, and broader discourses of our society. The reasons for this are too numerous to consider here, but I argue that one of these reasons is that we seldom present sociology as something anyone can do, or something that can be useful in everyday life. A curious sociology would be a sociology that offers not answers, dry facts, or abstract theories but instead would present sociology as an active practice that enables us to better integrate our experiences and understand the connections between different people, locations, and events. Second, a curious sociology promotes increased democracy, freedom, and autonomy. Here, I make no claims that sociology or curiosity can truly combat structural oppressions, enforced through material, political, and legal power. However, I do suggest that the practice of sociology encourages us to seek new connections, attempt new tasks, and reconsider our values at the same time as it increases our interest in values, norms, and ideals initially foreign to us. Sociology, in this sense, implies experimentation—the trying out of new selves and the creation of new means and ends. My conception of a curious sociology grows out of a particular understanding of the word sociology. Defining sociology is an inherently fraught exercise. Therefore, I wish to emphasize that I make no claim to a universal definition here, but instead merely offer some outlines of my own understanding. Sociology, for me, encompasses a manner of being, understanding, and acting in the world. It is an active, critical practice that involves both “an attempt to understand” (Berger 1963:4) and an acknowledgement that “to understand something is to acquire a way of doing something” (Crossley 2013:149). Sociology entails critically questioning the world around us as well as critically questioning ourselves, our taste and our actions. Sociology, in this sense, is therefore not solely something we do in our roles as researchers or teachers, but instead a habit [see e.g. James (1997)] that we can (and should) adopt in almost all social settings. Curiosity forms a part of this habit. I follow Dewey (1966) in viewing curiosity as the process through which we seek new connections to our experiences. Through curiosity, Dewey (1966:244) suggests that “our ordinary daily experiences cease to be things of the moment and [instead] gain enduring substance.” Like sociology, curiosity in this conception is active. Through this activity, our experiences become more significant, meaningful, and holistic. Like all habits, the practice of sociology must be learned. Thus, when discussing the role of sociology, the obvious place to start is in the classroom. Teaching sociology implies finding new and better ways to incorporate and expand the interests our students arrive with, demonstrating that sociological theories are not merely abstract ideas but instead concrete tools. For example, when teaching on deviance and stigma, I have found it helpful to ask students to observe and consider events they attend like family dinners, parties, or university lectures and create lists of rules or norms that govern these settings. I argue that it is less important to have an encyclopedic knowledge of Goffman, Becker, and their influences and more important how their writings allow us to analyze how power works in these varied settings, through examining who can and cannot stigmatize in these settings or whether different individuals suffer the same consequences for similar behaviors. In immediately making sociological theories concrete, I suggest that (at least some) students become more curious about why the social situations they find themselves in appear as they do and begin to reconsider how their experiences in these seemingly strikingly different places can be connected. Similarly, it can help students to query whether the rules, habits, and norms that regulate these social settings are desirable, and if not, what alternatives may exist or be imagined. The point, then, is not necessarily that students can recite the writings or theories of Durkheim, Collins, or Cohen (to remain with the criminological theme) but rather that they engage in the activity of questioning and wondering. Theories are, after all, merely tools we use to try to understand and explain the world around us. In focusing teaching on promoting the activity of sociology rather than the canon of sociology, I suggest that we may help our students to ask more questions, expand their horizons, and become more curious. Similarly, if we consider sociology as a habit rather than profession, I suggest that we must take seriously Martin’s (2022:39) claim that we often “do not carry out research to clarify issues about which we are unsure” and that we instead at times explore “questions…whose answers are so obvious that they are hardly worth asking.” One does not have to agree with Martin’s polemic stance on the current state of sociology to agree that research projects should start from a place of true doubt and curiosity. I suggest that one manner of ensuring that our research explores questions of both relevance and doubt would be to take the tenets of Dorothy Smith much more seriously than we often do. Departing from the experiences, problems, and questions of everyday life not only ensures that research remains rooted in concrete realities of actual subjects, but also enables us to pursue projects and questions that overlap between different spheres or fields of sociological research. Just as Mills famously argues that we should reject methodological fetishism, we should also reject theoretical or subfield fetishism. If we instead view sociology as a holistic activity, we can not only better connect the many varied and brilliant works of sociology that already exist, but also promote increased cooperation amongst different researchers, schools of thought, and even disciplines. Sociology, understood as an activity rather than a field, could play a vital role in understanding, changing, and improving our societies. The problems which we tend to examine in sociological research—poverty, sexism, racism, climate change, etc.—are not problems that individuals will solve. These are problems that can only be solved collectively. We require new solutions and will need to experiment with new forms of social organization. The activity of sociology is vital for imagining these new social arrangements as well as in helping us see if they solve our current problems and what new problems they might create. Promoting sociology as a curious activity means finding new ways to reach out to broader audiences at the same time as it means encouraging more individuals to engage in the activity of sociology, questioning and experimenting with the social orders they desire. In this sense, I end where I started, in agreement with Mills that the habit of sociology remains an invaluable aid not only in understanding our social world, but in changing it.   Colm FlahertyPostdoc at the Department of Social Sciences and Business, Roskilde UniversityUniversitetsvej 1, 14.1, DK-4000, Roskildecolmf@ruc.dk
Keywords: curious sociology; creativity; sociology